Crystal structure and copper ion emission properties of Rb4Cu16I7Cl13 solid electrolyte. (February 2022) - Abudouwufu, Tushagu; Zhang, Xiangyu; Zuo, Wenbin; Pelenovich, Vasiliy; Luo, Jinbao; Lan, Yueqiang; Tian, Canxin; Zou, Changwei; Tolstoguzov, Alexander; Fu, Dejun
Abstract: We present a study on structure and ion emission behavior of copper ion-conducting solid electrolyte Rb4 Cu16 I7 Cl13 prepared via mechano-chemical ball milling. The powder samples with varying milling time and rotation rate was studied. The room temperature ionic conductivity of Rb4 Cu16 I7 Cl13 was approximately with σrt ∼ 0.213 S/cm. The SEM morphology of this solid electrolyte was studied, and the larger particle sizes was estimated to be 1.3 μm. The thermal property was examined by differential scanning calorimetry, revealing a melting temperature of 229.7 °C. In addition, the ability to generate Cu + ion beams was also tested, and an ion current of 0.82 μA was obtained at 197 °C and 20 kV. It was observed that copper ions increase significantly with temperature and acceleration voltage. There is a good linear correlation between log(current) and the square root of the voltage, indicating that the emission current of copper ion from the tip of solid electrolyte abides by the Schottky model. A silicon sample was irradiated by the ion beam and copper nanoparticle were detected on the surface. Highlights: Solid electrolyte Rb4 Cu16 I7 Cl13 was synthesized by high-energy ball milling. Ion emitter with superionic conductor Rb4 Cu16 I7 Cl13 film was fabricated. The ion emission technique using the sharp Cu + conductive solid electrolyte film is presented. Characteristics and mechanism of Cu + ion-beam generation were studied. Synthesis of Cu nanoparticles was achieved via Cu + ion beam from the emitter.